COVID−19 hospitalization increases the risk of developing glioblastoma: a bidirectional Mendelian-randomization study - Dong, Jiajun; Wang, Shengnan; Xie, Haoqun; Mou, Yanhao; Zhu, Hao; Peng, Yilong; Xi, Jianxin; Zhong, Minggu; Xie, Zhengyuan; Jiang, Zongyuan; Wang, Kang; Chen, Hongyu; et al. (Frontiers in Oncology, 2023)
Background: As a result of the COVID-19 pandemic, patients with glioblastoma (GBM) are considered a highly vulnerable population. Despite this, the extent of the causative relationship between GBM and COVID-19 infection is uncertain.Methods: Genetic instruments for SARS-CoV-2 infection (38,984 cases and 1,644,784 control individuals), COVID-19 hospitalization (8,316 cases and 1,549,095 control individuals), and COVID-19 severity (4,792 cases and 1,054,664 control individuals) were obtained from a genomewide association study (GWAS) from European populations. A total of 6,183 GBM cases and 18,169 controls from GWAS were enrolled in our study. Their associations were evaluated by applying Mendelian randomization (MR) including IVW meta-analysis, MR-Egger regression, and weightedmedian analysis. To make the conclusions more robust and reliable, sensitivity analyses were performed.Our results showed that genetically predicted COVID-19 hospitalization increases the risk of GBM (OR = 1.202, 95% CI = 1.035-1.395, p = 0.016). In addition, no increased risk of SARS-CoV-2 infection, COVID-19 hospitalization and severity were observed in patients with any type of genetically predicted GBM.Our MR study indicated for the first time that genetically predicted COVID-19 hospitalization was demonstrated as a risk factor for the development of GBM.